(untitled) (American Journal of Islam and Society, 1985)
Today, Western philosophy is all too close to its origins because it has never really answered the questions that brought about its birth. These questions are: What is the meaning of life and death? What is the source and what is the vocation of our freedom? How to act in order to fulfill the patterns of God? Such essential questions of philosophy are raised only by man, and properly so. For only man cannot live without raising them. In nature, every being has a place and a function which are not of his own choosing. Every creature is subject to the law of God: a stone must fall when released, a plant must grow when nourished; an animal must follow its instinct. All of them obey and fulfill this divine law without choice or questioning. With man, however, a new realm begins. He is the only creature that God has endowed with the choice of either disobeying or fulfilling that law after a free, deliberate, and responsible decision. The Holy Qur’an says: “We have offered Our trust to the heavens, to earth and mountains. But they all rejected it in fear and trembling. Only man arose to accept and carry that trust. He alone is unjust and ignorant (33:72). It was thus that human history began, a history which man himself makes, unlike all other creatures which fulfill the law of necessity. In order to regain this lost unity, that is to say, in order to integrate him into the whole of creation, and thus give his life and death their place and meaning in the divine order, man created all sorts of myths. But he also received divine assistance through the revelations brought by the prophets of every people. In the sixth century after Christ, throughout Asia, the great myths of Mesopotamia and Egypt, the wise sayings of the Upanishads of India, and those of Chinese Taoism raised and considered the basic problems of the ultimate reality of this world, its meaning and significance, our role in it, ...